PENERAPAN TEORI GRAF PADA PERANCANGAN JALUR INSTALASI LISTRIK RUMAH SEDERHANA UNTUK OPTIMISASI PANJANG KABEL - Dian Yulis Wulandari (Universitas Islam Sumatera Utara, 2025)
Electrical installations in houses often experience cable waste due to suboptimal planning. This research applies graph theory with the Minimum Spanning Tree (Prim) algorithm to optimize electrical installation design in type 36 houses. The system is modeled as a weighted graph with vertices representing load points and edges representing cable routes. Results show the conventional method requires 31.50 meters of cable, while Prim's algorithm produces only 21.07 meters, achieving 33.11% savings (10.43 meters). The resulting network structure is acyclic and simpler, making it easier to implement and maintain. The design has been validated according to PUIL 2000 and SNI 04-6989.5-2000 standards. This research provides a systematic methodology for designing efficient, safe, and cost-effective electrical installations applicable to the residential construction industry.